2020
DOI: 10.1353/rhe.2020.0006
|View full text |Cite
|
Sign up to set email alerts
|

STEM Degree Completion and First-Generation College Students: A Cumulative Disadvantage Approach to the Outcomes Gap

Abstract: Part of the Higher Education Commons Recommended Citation Recommended Citation Bettencourt, Genia; Manly, Catherine A.; Kimball, Ezekiel; and Wells, Ryan, "STEM degree completion and first-generation college students. A cumulative disadvantage approach to the outcomes gap" (2020). Review of Higher Education. 35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 53 publications
(78 reference statements)
1
59
0
Order By: Relevance
“…For example, it would be informative to test for potential subgroup differences in the degree to which influence operates contemporaneously or longitudinally. Moreover, further study is needed on the degree to which TIMSI derived hypotheses hold for first- versus multi-generational students in STEM fields when accounting for the influence of pre-college factors [ 123 ]. In addition, the present study used a single and self-reported operationalization of social integration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it would be informative to test for potential subgroup differences in the degree to which influence operates contemporaneously or longitudinally. Moreover, further study is needed on the degree to which TIMSI derived hypotheses hold for first- versus multi-generational students in STEM fields when accounting for the influence of pre-college factors [ 123 ]. In addition, the present study used a single and self-reported operationalization of social integration.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, students who score higher on standardized college entrance exams, such as the quantitative Scholastic Aptitude Test (SAT) score, and students with higher high school grades are more likely to be retained in STEM (Chang et al, 2014;Redmond-Sanogo et al, 2016;Hughes, 2018;Park et al, 2020). Differences in precollege academic preparation help explain additional inequities beyond race/ethnicity; first-generation students are also less likely to complete STEM degrees, but first-generation students also on average score lower on standardized tests and grades, take fewer advanced high school math and science courses, and have less access to role models in STEM, such as a parent employed in a STEM field (Bettencourt et al, 2020).…”
Section: Factors That Predict Stem Retentionmentioning
confidence: 99%
“…These shortfalls are exacerbated by particularly low representation of women, some ethnic groups and low-SES individuals in many STEM fields, most notably the physical sciences, engineering, maths, and computing. In the United States, for example, Blacks make up 13% of the population and receive 10% of bachelor's degrees but only 4% of engineering bachelor's degrees (National Science Board, 2019), and while first-generation students are somewhat less likely than continuing-generation students to complete college with a degree in any subject (57% vs. 65%), the effect is significantly more pronounced with STEM degrees (9% vs. 15%) 6 (Bettencourt, Manly, Kimball, & Wells, 2020). In the United Kingdom, compared to 58% of graduates in all subjects (Higher Education Statistics Agency, 2020), only 15% of graduates in engineering, technology, and computer science, and only 12% of those working in engineering occupations are women (Neave et al, 2018;STEM Women, 2020).…”
Section: Inequalities In Educational Outcomes Vary By Contextmentioning
confidence: 99%